REVIEW DAN ANALISIS MAGNUS OPUS AL-SUYUTI DALAM AL-ITQAN FI ULUM AL-QUR’AN - Setiawan, Iwan (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2024)
This study analyzes al-Itqan fi Ulum al-Qur'an, a monumental work by Imam Jalaluddin al-Suyuthi, which is one of the main references in the study of Qur'anic sciences. The purpose of this study is to examine the systematics and contributions of Al-Itqan to the development of Qur'anic sciences. The study uses a library research method with a qualitative approach, utilizing primary and secondary sources in the form of books, journals, and articles. Data collection techniques include literature studies and qualitative analysis of the contents of Al-Itqan. The results of the study show that Al-Itqan presents a comprehensive discussion of the Qur'anic sciences, including the origins of verses, interpretations, laws, and linguistics. This book consists of 80 main discussions that are arranged systematically, covering: the place of revelation, time, conditions, sanad, asbabun nuzul, reading methods, and understanding the Qur'an. Its specialty lies in its scientific approach, easy-to-understand language style, and broad scope of material. This work also serves as an important foundation in understanding the context and implied meaning of the verses of the Qur'an, thus supporting learning in Islamic boarding schools and other Islamic educational institutions. Imam Suyuthi compiled this book against the background of the lack of works that studied the sciences of the Qur'an in depth in his time. Through Al-Itqan, he not only documented the existing sciences but also enriched the tradition of interpretation of the Qur'an. This makes Al-Itqan a mandatory reference in the study of the science of the Qur'an until now.